2011
DOI: 10.4104/pcrj.2011.00041
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on optimal care for patients with COPD

Abstract: Worldwide, clinicians face the task of providing millions of patients with the best possible treatment and management of COPD. Currently, management primarily involves short-term 'here-and-now' goals, targeting immediate patient benefit. However, although there is considerable knowledge available to assist clinicians in minimising the current impact of COPD on patients, relatively little is known about which dominant factors predict future risks. These predictors may vary for different outcomes, such as exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
2
21
0
5
Order By: Relevance
“…that patients with COPD may require hospitalisation (and/or die) for reasons not directly related to COPD (comorbidities). Because they are amenable to therapy [22], this observation supports the emphasis made by the 2011 GOLD document on the importance of actively looking for, and adequately treating if present, the comorbidities known to frequently occur in COPD patients [2]. 5) Since ECLIPSE does not have information on specific causes of death, we explored factors associated with increased risk of mortality (and hospitalisations) using a Cox proportional hazards regression model.…”
Section: Novel Observationsmentioning
confidence: 58%
“…that patients with COPD may require hospitalisation (and/or die) for reasons not directly related to COPD (comorbidities). Because they are amenable to therapy [22], this observation supports the emphasis made by the 2011 GOLD document on the importance of actively looking for, and adequately treating if present, the comorbidities known to frequently occur in COPD patients [2]. 5) Since ECLIPSE does not have information on specific causes of death, we explored factors associated with increased risk of mortality (and hospitalisations) using a Cox proportional hazards regression model.…”
Section: Novel Observationsmentioning
confidence: 58%
“…Ideally, they should serve to work towards 'optimal COPD care', based on the concept that here-and-now goals should be integrated with goals to improve long-term outcomes and reduce future risk. 1 However, this integration has (until recently) been overlooked, largely because multidimensional indices have usually been developed in selected patient groups and thus lack external validity in the community.…”
Section: Editorialsmentioning
confidence: 99%
“…It has been found that GPs intentionally avoid early diagnosis as a result of misperception of patients’ unwillingness to be given a diagnosis and their own pessimistic attitude to prognosis 4. To achieve ‘optimal’ COPD care, holistic management is proposed based on the concept that immediate goals should be integrated with goals to improve long-term outcomes 10. COPD has been described as ‘a story with no beginning’,11 as early symptoms are seen as a normal way of life 3,1113.…”
Section: Introductionmentioning
confidence: 99%